Answer:
Step-by-step explanation:
24 p=72
-3.4, -1.5, 0, 1/2, 8.5, and 8.45
Hope this helped:))
Answer:
si quieres la respuesta pon más puntos
Answer:
Step 1 Eliminate fractions by multiplying all terms by the least common denominator of all fractions.
Step 2 Simplify by combining like terms on each side of the inequality.
Step 3 Add or subtract quantities to obtain the unknown on one side and the numbers on the other.
Answer:
f(-2) = -5
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x + 1
f(-2) is x = -2
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em>: f(-2) = 3(-2) + 1
- Multiply: f(-2) = -6 + 1
- Add: f(-2) = -5